Rapid synthesis and magnetic property characterization of Mg2+ doped Co3O4 nanostructures. Issue 7 (3rd July 2022) - Sundararajan, M.; Vidhya, J.; Revathi, R.; Sukumar, M.; Arunadevi, B.; Rajkumar, R.; Ramachandran, S.; Kamalakannan, M.; Dash, Chandra Sekhar; Rajabathar, Jothi Ramalingam; Arokiyaraj, Selvaraj
Abstract: Utilizing combustion method Mg substituted Co3O4 nanoparticles were prepared using the fuel L-alanine. The formation of the cubic spinel structure in the prepared undoped Co3O4 and Mg substituted Co3O4 is assured by X-ray diffraction (XRD) studies. The average crystallite size was observed to lie within 48.6 nm to 17.3 nm. The microstructural analysis shown that the prepared nanoparticles are porous in nature comprising of intragranular pores and melded grains with distinct grain boundaries. The bandgap values were determined using Kubelka–Munk (K–M) technique which was found to fall within 1.87–3.64 eV range. Interestingly, para-/superpara- magnetic characteristics was seen at ±15KOe by the magnetic studies. The FT-IR bands at 662 and 569 cm −1 are attributed to the Co–O stretching mode of cubic spinel Co3 O4 structure for the prepared samples. .